2017
DOI: 10.1093/toxsci/kfx232
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Effects of Cannabidiol and Δ9-Tetrahydrocannabinol in Zebrafish

Abstract: Cannabidiol (CBD) has gained much attention in the past several years for its therapeutic potential in the treatment of drugresistant epilepsy, such as Dravet syndrome. Although CBD has shown anecdotal efficacy in reducing seizure frequency, little is known regarding the potential adverse side effects of CBD on physiology, development, organogenesis, or behavior. The goal of this project was to compare the relative morphological, behavioral, and gene expression phenotypes resulting after a developmental exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 57 publications
(71 reference statements)
4
57
0
1
Order By: Relevance
“…Previous findings point to a role of the eCB system in zebrafish development (Akhtar et al, 2013(Akhtar et al, , 2016Carty et al, 2017;Oltrabella et al, 2017;Watson et al, 2008). For instance, reduced gene expression for the CB 1 R results in a number of deficits in axonal growth, neuronal branching and fasciculation of hindbrain neurons that are known to express the CB 1 R (Watson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings point to a role of the eCB system in zebrafish development (Akhtar et al, 2013(Akhtar et al, , 2016Carty et al, 2017;Oltrabella et al, 2017;Watson et al, 2008). For instance, reduced gene expression for the CB 1 R results in a number of deficits in axonal growth, neuronal branching and fasciculation of hindbrain neurons that are known to express the CB 1 R (Watson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The THC contained in marijuana may have similar effects as endogenic cannabinoids that activate cannabinoid receptors for self-defense mechanisms, whereas the CBD contained in marijuana may have a role in the regulation of other cannabinoids including THC. Previous studies revealed the developmental effects of CBD and THC in zebrafish; however, further studies are needed to assess the latent effects [58]. The proportions of cannabinoids are different because many Cannabis plants grow naturally.…”
Section: Discussionmentioning
confidence: 99%
“…For example, extracellular serotonin content has been reported to have contrasting effects on anxiety in the same adult zebrafish species [72,80]. Larvae, in contrast to their adult counterparts, exhibit a transient elevation in motor activity in response to sudden onset of darkness [53,64,81]. Dark avoidance was shown to be modulated by anxiolytic drugs such as the 5-HT1A agonist, buspirone, which increased dark preference patterns in zebrafish larvae [81].…”
Section: Discussionmentioning
confidence: 99%